A Comparative Study on Oxygenating Capacity of Terumo Pediatric Oxygenator vs Dideco Pediatric Oxygenator - Chaudhary, SN; Ghatta, M; Khan, U (Nepalese Heart Journal, 2004)
This study shows the comparative analysis on oxygenating capacity of two brands of oxygenators: DIDECO Midiflow D705 and TERUMO Capiox 5X10. This study is based on the arterial blood gas analysis which was done during cardiopulmonary bypass. The data was obtained from perfusion data sheet available at SGNHCG. 71 DIDECO and 55 TERUMO oxygenators and altogether 335 arterial blood gas samples were considered for the study.